AgNO3-Catalysed intramolecular cyclization: access to functionalized cyclopentanones and spiro-cyclopentanones - Bhoite, Shubhangi P.; Bansode, Ajay H.; Burate, Pralhad A.; Suryayanshi, Gurunath (Asian Journal of Organic Chemistry, 2019)
An efficient AgNO3-catalysed method has been developed for the synthesis of functionalized cyclopentanones and spiro-cyclopentanones through intramolecular cyclization between ynones and cyanoacrylate/aryl/alkylidene malononitrile using DBU as a base. Easy availability of starting materials and mild reaction conditions makes this protocol more feasible over previously reported methods. The functionalized cyclopentanones and spiro-cyclopentanones were synthesized in good to excellent yields with a broad substrate scope.